2012
DOI: 10.5114/aoms.2012.29521
|View full text |Cite
|
Sign up to set email alerts
|

Is plasma urotensin II concentration an indicator of myocardial damage in patients with acute coronary syndrome?

Abstract: A b s t r a c tIntroduction: Urotensin II (UII) is a vasoactive peptide secreted by endothelial cells. Increased plasma UII concentration was observed in patients with heart failure, liver cirrhosis, diabetic nephropathy and renal insufficiency. In patients with myocardial infarction both increased and decreased plasma UII concentrations were demonstrated. The aim of this study was to analyze whether plasma UII concentration reflects the severity of acute coronary syndrome (ACS). Material and methods: One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In addition to its vasoconstrictor effects, these studies performed on the cardiovascular system have demonstrated that UII can affect the pathogenesis of atherosclerosis (17) and induce fibrosis, cardiac hypertrophy, and coronary vasoconstriction (18). Contrary to these unfavorable data (17,18), Babińska et al (19) documented the potential cardioprotective effects of UII. In another study (20), it was shown that UII ameliorates reperfusion injury in ischemic heart disease.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition to its vasoconstrictor effects, these studies performed on the cardiovascular system have demonstrated that UII can affect the pathogenesis of atherosclerosis (17) and induce fibrosis, cardiac hypertrophy, and coronary vasoconstriction (18). Contrary to these unfavorable data (17,18), Babińska et al (19) documented the potential cardioprotective effects of UII. In another study (20), it was shown that UII ameliorates reperfusion injury in ischemic heart disease.…”
Section: Discussionmentioning
confidence: 90%
“…It is widely known that hypertension affects UII level; this subject has been investigated in many studies (6,19). In some studies, increased UII levels have been reported (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urotensin II has been used as a marker of myocardial injury and ischemia reperfusion injury (23,24). In a previous study, urotensin II levels were found to be increased in smokers but the relationship between this marker and varenicline has not been considered so far (25).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this peptide may contribute to the physiological regulation of cardiovascular homeostasis in humans (21,22). It was suggested that urotensin II can be used as a marker of myocardial and ischemia reperfusion injuries (23,24). Previously, it was shown that plasma urotensin II levels increased in smokers (25).…”
mentioning
confidence: 99%